(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت تجارب لدراسة تأثير المعاملة بتراكيز مختلفة من ثنائي الأمين Putrescine والمثبط MGBG على نمو وإنتاج البطاطا المروية بمياه ذات تراكيز مختلفة من الملوحة( (E.C:0.328-2.5-5 mm/cm . أظهرت النتائج, أن الري بمستويات مختلفة من الملوحة, قد خفض من معدل النمو الخضري للنباتات., كما أدت المعاملة بالPutrescine إلى زيادة معنوية في وزن الجذور الجافة, وفي عدد الدرنات ووزنها الرطب, ونسبة المادة الجافة, وكذلك محتوى النباتات من بعض العناصر الغذائية (الآزوت, الكالسيوم, المغنيزيوم ). بالنسبة لتأثير المعاملة بالMGBG فقد كان معنويا فقط بتأثيره على محتوى النباتات من بعض العناصر الغذائية( الآزوت- الكالسيوم- المغنيزيوم)ا. أظهرت تحاليل التربة المعاملة بكلا المركبين(MGBG- Putrescine) انخفاض معنوي في قيمة النا قلية الكهربائية لمحلول التربة, مما يدل على تنشيط هذين المركبين لامتصاص أملاح التربة. The effect of different concentrations of the diamine putrescine (Put) and the inhibitor (MGBG) on the development and the production of Potato watered by several concentrations of saline water (E.C = 0.328, 2.5, and 5 mm/cm), was studied. The results showed that the use of different concentrations of salinity decreased the vegetative growth of the plants. The treatment by putrescine led to significant increase in the weight of dry roots, the number and the net weight of the tubers, the percentage of the dry material in the tubers, and the plant contents of N, Ca, and Mg. treatment by the MGBG was significant only on the plant contents of N, Ca and Mg. The analysis of the soil treated separately by the products Putrescine and MGBG showed a significant decrease of the electrical conductivity(E.C) of the soil solution indicating that these products activated the absorption of salt.